(untitled) (History Journal «Jerónimo Zurita», 2022)
The aim of this article, which uses Ramón Via’s biography as a case study, is to show the key role of foreign soldiers in the transnational antifascist networks during the Second World War. Vía was a young Spanish communist who, after the battlefield war in Spain (1936-1939), played a key role building a transnational antifascist network in Argelia between 1939 and 1944. This network was able to connect international activists and soldiers in USA, Algeria, France, Italy, and Spain. The study uses to different approaches. On the one hand, it uses a global history approach, paying especial attention to two key elements: mobility and connectivity. On the other hand, it uses a microhistory approach, focusing on the biographical trajectory of an individual.